An Analysis of Poetic Devises and Symbolism Used in Emily Dickinson’s ‘Because I could not stop for Death’ - Khan, Yasmin Bibi (IJRDO - Journal of Social Science and Humanities Research, 2020)
Emily Dickinson’s ‘Because I could not Stop for Death’ is one of the most celebrated and researched poems in American literature. This research paper not only aims at analyzing thepoem stylistically by exploring the figurative language and poetic devices used by the poet to portray the themes of death and immortality; but it is also an attempt to find out the contextual meaning of each figure of speech used in the poem. Descriptive qualitative research method is used in the current study to analyze the poem. The findings revealed that while writing her poems Emily broke the norm of conventional style of composing poetry by adopting a unique form. One such example is the use of half rhyme instead of full rhyme. Moreover, figures of speech such as Personification, metaphor, metonymy, antithesis, symbolism etc. are used which will help the reader understand the poem.